Frota própria versus serviço de transporte terceirizado: um estudo comparativo na Universidade Federal da Fronteira Sul através do custo total de propriedade - Agostini, Lidiane Bassi (2017)
Studies on Total Cost of Ownership are still reduced in light of their relevance to a buying decision in organizations. Therefore, the present study aims to evaluate the total cost of ownership model as alternative sales and outsourced transportation service at the Federal University of the Southern Frontier camp Chapecó-SC. The research is limited to the comparison of the results obtained from the application of the total cost of ownership in the period from 2011 to 2025, insofar as it is not outsourced transportation service our products selected by a non-probabilistic and intentional sample. The fleet itself is composed of three vehicles, while the transport services are composed of two passenger vehicles. A methodology used in the research and case study. The results suggest that the outsourced transportation service is more economically attractive than a vehicle acquisition for its own fleet.